Validation of a Short Form for Health Literacy Assessment Using Talking Touchscreen Technology - Slesinger, Noël C. (Health Lit Res Pract, 2020)
BACKGROUND: Health literacy is an area of growing research and clinical interest, necessitating short, accurate measures of this complex construct. Health Literacy Assessment Using Talking Touchscreen Technology (Health LiTT) measures prose, document, and quantitative literacy by self-administration on a touchscreen computer. OBJECTIVE: The objective of this study was to assess the validity of a short form of Health LiTT and to identify a meaningful cutoff score for adequate health literacy. METHODS: A subsample of 137 participants from the Literacy and Cognitive Function among Older Adults study completed a 10-item Health LiTT short form and three interviewer-administered health literacy measures: Test of Functional Health Literacy in Adults (TOFHLA), Rapid Estimate of Adult Literacy in Medicine (REALM), and Newest Vital Sign (NVS). Convergent validity was assessed by correlating scores for all measures, and known-groups validity was assessed by comparing mean Health LITT scores across TOFHLA levels (inadequate, marginal, adequate). Internal consistency reliability was estimated with Cronbach's alpha. A cutoff score for adequate health literacy was established using the TOFHLA cutoff for adequate versus inadequate/marginal health literacy. KEY RESULTS: Spearman correlations between Health LiTT scores and total TOFHLA, REALM, and NVS scores were 0.65, 0.69, and 0.56, respectively (all p < .001). Mean Health LiTT scores were significantly and meaningfully different across inadequate (40.4), marginal (50.1), and adequate (57.1) TOFHLA categories (F = 60.6; p < .001). Cronbach's alpha for the Health LiTT short form was .73. A cutoff score of 55 on Health LiTT showed acceptable sensitivity and specificity to identify adequate health literacy. CONCLUSIONS: This 10-item Health LiTT short form demonstrated excellent convergent and known-groups validity and acceptable internal consistency reliability in older adults. The established cutoff also showed excellent sensitivity and specificity. Validation of other custom Health LiTT short forms with varying items from the bank and computer adaptive test-generated Health LiTT scores is ongoing. [HLRP: Health Literacy Research and Practice. 2020;4(4):e200–e207.] PLAIN LANGUAGE SUMMARY: This article provides evidence of the need for and psychometric properties of a valid and reliable short form of the flexible, technologically advanced Health Literacy Assessment Using Talking Touchscreen Technology measure, as well as a cutoff score to note adequate versus marginal/inadequate health literacy.